Probing the role of ceramide hydroxylation in skin barrier lipid models by 2H solid-state NMR spectroscopy and X-ray powder diffraction - Kováčik, Andrej; Vogel, Alexander; Adler, Juliane; Pullmannová, Petra; Vávrová, Kateřina; Huster, Daniel (Biochimica et biophysica acta. Biomembranes, 2018)
In this work, we studied model stratum corneum lipid mixtures composed of the hydroxylated skin ceramides N-lignoceroyl 6-hydroxysphingosine (Cer[NH]) and α-hydroxylignoceroyl phytosphingosine (Cer[AP]). Two model skin lipid mixtures of the composition Cer[NH] or Cer[AP], N-lignoceroyl sphingosine (Cer[NS]), lignoceric acid (C24:0) and cholesterol in a 0.5:0.5:1:1 molar ratio were compared. Model membranes were investigated by differential scanning calorimetry and 2H solid-state NMR spectroscopy at temperatures from 25 °C to 80 °C. Each component of the model mixture was specifically deuterated for selective detection by 2H NMR. Thus, the exact phase composition of the mixture at varying temperatures could be quantified. Moreover, using X-ray powder diffraction we investigated the lamellar phase formation. From the solid-state NMR and DSC studies, we found that both hydroxylated Cer[NH] and Cer[AP] exhibit a similar phase behavior. At physiological skin temperature of 32 °C, the lipids form a crystalline (orthorhombic) phase. With increasing temperature, most of the lipids become fluid and form a liquid-crystalline phase, which converts to the isotropic phase at higher temperatures (65-80 °C). Interestingly, lignoceric acid in the Cer[NH]-containing mixture has a tendency to form two types of fluid phases at 65 °C. This tendency was also observed in Cer[AP]-containing membranes at 80 °C. While Cer[AP]-containing lipid models formed a short periodicity phase featuring a repeat spacing of d = 5.4 nm, in the Cer[NH]-based model skin lipid membranes, the formation of unusual long periodicity phase with a repeat spacing of d = 10.7 nm was observed.
Keywords: Lipid packing; Temperature; Lipid Bilayers; rentgenové záření; Hydroxylation; hydroxylace; Thermotropic phase behavior; Cholesterol; lipidové dvojvrstvy; magnetická rezonanční spektroskopie; Magnetic Resonance Spectroscopy; Ceramides; Powder Diffraction; kůže; Models, Biological; Cell Membrane Permeability; Model membranes; permeabilita buněčné membrány; Skin Temperature; Deuterium; cholesterol; lidé; Order parameter; biologické modely; Skin; Humans; ceramidy; Hydroxylated skin ceramides; prášková difrakce; teplota; deuterium; X-Rays; teplota kůže